Maternal migration and child well-being in Peru - Escobal, J; Flores, E (Young Lives, 2009)
Migration affects not only those who migrate, but may also have intergenerational effects on their children. Looking at those mothers with a history of internal migration who are part of the Young Lives project, and comparing them with suitable controls, we find that mothers’ migration has had a positive impact on the nutritional outcomes and cognitive achievement of their offspring. However, we also find that there are heterogeneous impacts, as different types of migration trajectory (rural to rural; rural to urban – to intermediate cities or to the capital, Lima) can be associated with the prevalence of different channels affecting child wellbeing. Those channels are the income channel, as migration may lead to new incomegenerating opportunities; the information channel, as migration may allow the mother to access more information about child-care and health-related practices; and the access to services channel, as migration may facilitate or hinder access to key public services.